Employee silence and the authoritarian personality. Issue 1 (9th March 2015) - Timming, Andrew R; Johnstone, Stewart
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to, drawing from Adorno et al.'s (1950) The Authoritarian Personality, explain why some workers reject participation in decision-making on principle, preferring instead to defer to managerial authority and remain silent. Design/methodology/approach – The paper reviews the literatures on employee voice and silence and then builds a conceptual framework that can be used to explain employee silence in relation to personality structures. Findings – It is argued that some employees have personality structures that make them more susceptible to anti-democratic thoughts. Potentially fascistic personalities, as measured by the F-scale, are expected to derive pleasure in submission to the will of management. Research limitations/implications – The paper has implications for political and social psychologists, especially those seeking to understand how best to promote employee voice in the workplace. Originality/value – This study makes an original contribution to the employee voice and silence literatures by being among the first of its kind to examine the political psychology of fascism in the micro-context of the workplace.